Becoming the Shadows - Chris Comerford; Tracey Woolrych (M/C Journal, 2025)
Introduction The dark silhouette of Batman (Robert Pattinson) emerges from the shadows on a rainy night, confronting a gang at a train station. One of their members asks, “what the hell are you supposed to be?”, before moving to attack. Batman quickly disarms the gang member, but in contrast to many of the character’s incarnations – on the screen and the comic book page – who would knock the criminal out before moving on, this Batman pummels the gang member even after he’s been knocked to the ground. With a throaty growl Batman responds, “I’m vengeance”, then proceeds to violently assault the other gang members. So begins The Batman, director Matt Reeves’s 2022 adaptation of the Caped Crusader. In addition to the title character’s willingness to inflict violent punishment beyond the boundaries of how the character usually operates, the film inhabits a cinematic realm blending aspects of the noir and gothic genres similar to Tim Burton’s original Batman film (1989) and the Christopher Nolan Dark Knight trilogy (2005-2012). Where The Batman most stands apart from the other cinematic adaptations is its willingness to imbue the main character with traits that arguably deconstruct him as a psychologically damaged yet overly empathetic vigilante, at once alienated from his colleagues yet yearning for connection in a way other cinematic Batmen have not. Compounding this characterisation is the use of gothic and noir tropes which combine in intriguing subversions; Batman embodies the noir role of the dark detective with a chip on his shoulder headed for a bad end, yet is ensnared by the gothic’s connection to trauma and the uncanny as a figure of horror born of grounded, relatable injury. In a further twist of expected conventions, despite Batman’s arguably psychopathic traits and the dark, gloomy atmosphere suggesting that bad end, the film concludes with optimism, hope, and personal growth, suggesting a casting-off of the noir and gothic aspects in favour of psychological healing. In this article we discuss the intriguing dichotomy of The Batman as noir, gothic, and more besides from perspectives of media studies and psychology. We outline how both the noir and gothic genres inflect the film and the title character with expected conventions and qualities that are drawn from psychological aspects of empathy, trauma, and personal distress, and how the film presents a version of Batman working through these issues and who may end up a more stable, sane psychopath than the others who have worn the mantle on the big screen. Finally, we conclude by theorising what a gothic noir reading of Batman implies for the larger state of the character – and the uniqueness of Pattinson’s on-screen version of the character – and for understanding anti-heroism more broadly as a staple of the noir genre. Batman as Gothic Noir Character Our research locates Pattinson’s Batman at an intersection of two neighbouring genres. The first is of course film noir, concerned with the use of the “hard-boiled detective” and associated tropes – the femme fatale, focus on crime and murder, dark-hued cinematography, and so on. While previous Batman media have included noir stylings and influences, arguably The Batman is the first on-screen adaptation of the character to fully embrace and embody the genre compared to previous uses of camp (Batman: The Movie, 1966, and Batman and Robin, 1997), post-9/11 “terror tv” (The Dark Knight, 2008) and the gothic (Batman, 1989, and Batman Returns, 1992). This latter genre is the second cross-point of The Batman, with the film drawing upon gothic tropes more aligned with the abject, grounded repulsion of human- and self-based horror than with the fantastic and somewhat distanced gothic tropes inherent to the monster and vampire fiction subgenres. In essence, The Batman presents a superhero embroiled in the noir atmosphere of a crime-ridden Gotham whilst dealing with the personal horrors inflicted upon himself and those around him as a gothic protagonist. In a manner similar to Blade Runner’s (1982) combination of film noir and sci-fi, The Batman integrates its film noir tropes into the superhero genre. There is an initial thematic dissonance at work in this fusion, given the wish-fulfilment aspect of the superhero – a figure we may wish to embody or emulate as well as look up to – clashing with the distanced, emotionally isolated nature of the noir protagonist. Very few viewers could say they would want to be Pattinson’s Batman, given how alienating and emotionally bereft he is. Where emulation may be employed is in the desire for exacting justice upon the unjust through Batman’s vigilantism, offering a figure of power and agency that audiences can engage with despite him being an extrajudicial figure (Brooker; Langley; Comerford “The Hero”). In the film, Pattinson’s Batman does not yet enjoy the implicit acceptance of his vigilantism by law enforcement which characterises many of his adaptations; his relationship with Lieutenant Gordon (Jeffrey Wright) is fraught and the Gotham Police Department has a tenuous partnership with him. While he is what Jacques Derrida would consider to be a pharmakon, a figure who alternately helps and hurts Gotham’s situation through his action as both “a remedy and a poison” (Derrida and Johnson 73), he is not legitimated as a necessary tool of dispensing justice. This means Batman is not yet the figure of the state of exception (Agamben) which enables him to undertake crimefighting as an extraordinary extrajudicial practice necessitated by crisis, something which is again inherent to the Batman adaptations mentioned previously. Instead, Pattinson’s Batman hews much closer to the figure of an anti-heroic noir protagonist, “a lone hero, usually some kind of detective or investigator” operating in a city “portrayed as vile and evil … where people are sinful and untrustworthy … abounding in crime” (Flisfeder 103-4). His status as a nascent vigilante waging a one-man war on crime illustrates him as an outsider even before the film explores Bruce Wayne’s tortured psychology and emotional isolation. It is because of this isolation that Pattinson’s Batman is made more complex through the addition of the gothic to the noir. It is made clear through his actions and his narrated entries in his journals that Batman sees himself as becoming an embodiment of fear and violence necessary to secure Gotham; in effect, becoming a monster to stop the monsters. Gothic tropes of inhuman horrors and fear of the unknown marry monstrosity and abjection, a terror made of humanity yet exaggerated into almost mythic status through symbols and disbelief (see Punter; Spooner). Batman makes a conscious effort to be a monstrous symbol of violence to criminals, manifested in a scene where a criminal sees the light of the Batsignal in the sky and runs in fear of a darkened road where he believes Batman may be waiting. Aside from Gotham being a crime-riddled hellhole, Batman’s actions are driven by internal horror and an inability to emotionally process his trauma after seeing his parents murdered at a young age, a trauma which in the gothic tradition haunts him as an inescapable facet (Punter and Byron). His surrogate father figure and butler, Alfred Pennyworth (Andy Serkis), aids Batman in fighting crime and attempts to do the same for his emotional maturation and growth, but Bruce rejects Alfred’s attempts to help as anything other than an aide to Batman’s campaign. A strand of The Batman’s narrative concerns Bruce’s eventual attempt to overcome his emotional isolation and realise his ability to do more than just break bones and scare people. In this manner the gothic as a genre of exploring trauma (Hogle) is also utilised to add to Batman’s nuances. While Pattinson’s Batman arguably improves emotionally by the end of the film, potentially breaking free from the “noir lone hero” archetype and into something still gothic yet healing, the journey to arrive at that conclusion spells out troubling facets of the character that are sharpened through the combination of the gothic and noir genres. Though many interpretations of the character strongly imply a close connection between Batman’s actions and the murderous antics of the villains he faces – arguing that he is only one bad day away from joining them in Arkham Asylum (Morrison) –, rarely has there been a version of the character that embodies so starkly many elements of outright psychopathy. Conflicted Sense of Self-Help through Hurt and the “Empathy Cost” Problem Batman, a dark and brooding figure with a dearth of emotions and penchant for violence, encapsulates the hallmarks of a psychopath. Using Hare et al.’s (394) Psychopathy Checklist Revised (PCL-R), this anti-hero would score highly on several criteria, including shallow affect, lack of remorse/guilt, criminal versatility, and the need for stimulation. However, many other criteria would not be met (e.g., pathological lying; conning/manipulative; superficial charm), meaning they would fall below the threshold of clinical psychopathy. Psychopathy is most known for its association with a lack of empathy and callous/unemotional traits (Hare et al. 392). On the surface Batman would seem to be high on these criteria; however, we argue this may not be the case. What Batman does display are characteristics of boldness (calmness under pressure or threat; high self-assurance; tolerance for danger; thrill seeking) and meanness (excitement seeking; empowerment through cruelty; Patrick et al. 926-8). These traits are synonymous with the primary psychopath: one who demonstrates low anxiety and social effectiveness (Patrick et al. 918). Batman also embodies other dark traits from the constellation of Dark Triad characteristics (Jonason et al. 194; Greenwood et al. 166). This construct represents personality traits (psychopathy, narcissism, and Machiavellianism) that are often thought of as negative and maladaptive (Jones and Paulhus 28). Born of trauma, Batman demonstrates high levels of aggression, antisociality, and grandiosity through being special and entitled (Jonason et al. 193; Wang 1007), personality factors that are most often associated with narcissism and psychopathy. However, the presence of these ‘dark’ traits does not necessarily exclude other positive characteristics, such as empathy, which add to the complexity of his gothic noir characterisation. Heym et al. identified a cluster of individuals high in both dark traits and empathy. The Dark Empath displays selfish and untrusting or contentious behaviours, despite the high levels of empathy. Whilst lower in aggression than the Dark Traits cluster (low empathy, high dark traits) the dark empath still displays higher levels of aggression than typical (Heym et al. 7). Batman does not strictly adhere to all of Heym et al.’s (8) dark empath qualities, being higher in interpersonal aggression; however, this research demonstrates that, in the real world at least, psychopathy, narcissism, and empathy are not all mutually exclusive. Whilst Batman comes across as unempathetic and unemotional, these qualities are, like the one he dons, a mask. His empathy is targeted towards those few who are close to him and those whom he deems worthy of it: respectively, Alfred and the citizens of Gotham City. Importantly, Batman denies himself compassion and empathy, and does not expect it in return, something in keeping with noir tropes of the loner hero. By compartmentalising these emotions, he distances himself from humanity, de-humanising himself. This is a protective mechanism that grants freedom for him to commit the highly violent acts he does, in order to bring ‘justice’ to those who deserve it; the cost of being the ‘hero’ is that he cannot indulge in the human condition, for to do so completely would be to see himself as a true monster. In this way, Batman portrays himself as unfeeling, uncaring (to a degree), and a psychopath. The juxtaposition of both Batman and the film’s primary villain, The Riddler (Paul Dano), as two different types of psychopaths not only imbues the film with an unrelentingly dark tone – again, in keeping with many other film noir texts – but also blurs the lines between pure good and pure evil. The Riddler, whilst embodying more of Hare’s psychopathic traits, is still enacting vengeance against corrupt officials, which could possibly be seen as a type of heroism. But viewers lack an affinity for The Riddler the way they do for Batman, given that the former’s mental instability takes him beyond the reach of ‘normal’ understanding. Whilst Batman is ruthless, The Riddler is more so, garishly displaying his gruesome punishments for the whole city to see. It is both warning and theatre. The Riddler revels in his ability to unnerve, regardless of the cost to others, as is demonstrated in his disregard for safety when attacking the funeral of Don Mitchell Jr. (Rupert Penry-Jones). Batman at least has some redeeming qualities, though they are few. He saves children and innocents, and demonstrates care towards others – albeit a limited number – such as Alfred and the Catwoman (Zoe Kravitz). His inability to protect Alfred is a cause of angst and anguish for him, making him strive harder to find the one responsible. He tries to protect Catwoman by convincing her not to kill the cop, knowing that she will ‘never come back’ from that; in a twist on noir tropes, Catwoman as the typical femme fatale becomes a figure of redemption rather than a cause of the hero’s downfall or a tragic murder victim. But the miasma of despair and fear that seems to follow Batman makes connections otherwise difficult. Even those who need to work closely with him, such as Gordon and the GCPD, are uncomfortable in his presence, resulting in further isolation of the anti-hero (Sánchez and Vidal-Mestre 256). This perceived lack of empathy, the absence of emotional displays, the difficulty with connections, and the inability to relate to people can be seen as character flaws, emphasising the anti-heroic nature of the character (Wang 1006). In this case though it is arguable that each of these is a deliberate conscious choice Batman makes. He does this in order to become the monster he believes he needs to be, undertaking a sacrifice to be the saviour of Gotham. It is a mistake to believe Pattinson’s Batman lacks empathy, whether as a deliberate choice to excise it or not. A lack of empathy would mean he would not understand another’s pain or distress. Instead, he has an over-abundance of emotional empathy. Davis (118) defines empathy as having both cognitive and affective elements, such as empathic concern (concern and compassion for others) and personal distress (the discomfort you feel in the face of another’s distress). Batman experiences a great deal of personal distress, feeling the pain of others acutely. In part this is what drives him: that desire to relieve not only others’ pain, but his own. Empathy is also commonly associated with morality, or more precisely moral action (see Hoffman 221). Whilst Batman obviously has a moral code, that code is fluid and malleable – also a distinctly noir trait, for the loner hero willing to break the legal and moral rules to succeed. For instance, Batman will work with criminals in order to fulfil his goals, although his distaste in doing so is obvious. This moral fluidity, and his code of the end justifying the means, places Batman in morally ambiguous territory, underpinning his dark persona of ruthlessness, and reinforcing his noir anti-hero positioning (Sánchez and Vidal-Mestre 256; Wang 1006). Batman is what Comerford (“Ambiguous” 4) refers to as a liminal hero, inhabiting the spaces between the black and the white. In true noir fashion, Batman stalks the grey areas between hero and villain, between good and evil, between empath and psychopath. Whilst traditionally these latter two concepts sit diametrically opposed, as demonstrated in Heym et al.’s (7) research, they can be found together in the dark empath. Batman is able to be both aggressive and empathetic by compartmentalising his empathy and walling off his emotions. His high emotional empathy acts as the motivator for violence to protect those he sees as innocent. But as we can see, navigating this liminal emotional space comes at a high cost. Conclusion: A Hopeful Batman? We have examined noir and gothic facets of both Batman and The Batman through brief explorations of media studies and psychology, arguing that the film and this version of the character offer a unique representation of a character traditionally associated with darkness. The Batman combines gothic tropes of horror and gruesomeness with noir tropes of the ‘hard boiled’ detective, as Batman seeks to bring to justice Gotham’s latest serial killer, the Riddler. This iteration of Batman embraces his anti-heroism, engaging in extreme acts of violence in order to visit justice upon the unjust. With its sepia tones and dreary atmosphere, this film pushes the limits of the liminal hero, leveraging both the noir and the gothic to portray a dark study of the tortured human condition. Concurrently, the film ends with what is arguably an optimistic ending. Bucking common film noir trends, Batman does not die, nor does he become relegated to the fringes of society as a loner once more, but instead he is embraced by the public as a hero, saving them from the breaching of the Gotham sea wall. Gothically speaking, while Bruce Wayne’s trauma is still present, he has shown promising signs of healing through his horror, evidenced by his willingness to mend his relationship with Alfred. As if to underscore this optimism, Batman’s final scenes feature him – a nighttime vigilante usually occupying the shadows – standing in daylight. References Agamben, Giorgio. State of Exception. Chicago: U of Chicago P, 2005. Brooker, Will. Hunting the Dark Knight: Twenty-First Century Batman. London: I.B. Tauris, 2012. Comerford, Chris. “Ambiguous Heroism: Anti-Heroes and the Pharmakon of Justice.” IM: Interactive Media 1.11 (2016): 1-13. ———. “The Hero We Need, Not the One We Deserve: Vigilantism and the State of Exception in Batman Incorporated.” Graphic Justice: Intersections of Comics and Law. Ed. Thom Giddens. Oxon: Routledge, 2015. 183-200. Davis, Mark H. Empathy: A Social Psychological Approach. Routledge, 2018. Derrida, Jacques, and Barbara Johnson. Dissemination. Chicago: U of Chicago P, 1981. Flisfeder, Matthew. Postmodern Theory and Blade Runner. New York: Bloomsbury, 2017. Giddens, Thom. “Natural Law and Vengeance: Jurisprudence on the Streets of Gotham.” International Journal for the Semiotics of Law 28 (2015): 765-785. Greenwood, D., Angelique Ribieras, and Allan Clifton. “The Dark Side of Antiheroes: Antisocial Tendencies and Affinity for Morally Ambiguous Characters.” Psychology of Popular Media 10.2 (2021): 165–177. Hare, Robert D., Stephen D. Hart, and Timothy J. Harpur. "Psychopathy and the DSM-IV Criteria for Antisocial Personality Disorder." Journal of Abnormal Psychology 100.3 (1991): 391. Heym, Nadja, Fraenze Kibowski, Claire A.J. Bloxsom, Alyson Blanchard, Alexandra Harper, Louise Wallace, Jennifer Firth, and Alexander Sumich. "The Dark Empath: Characterising Dark Traits in the Presence of Empathy." Personality and Individual Differences 169 (2021): 110-172. Hogle, Jerrold.E. “History, Trauma and the Gothic in Contemporary Western Fictions”. The Gothic World. Eds. Glennis Byron and Dale Townshend. Oxon: Routledge, 2014. 72-81. Hoffman, Martin L. "Empathy, Social Cognition, and Moral Action." Handbook of Moral Behavior and Development. Psychology Press, 2014. 275-302. Jonason, Peter K., Gregory D. Webster, David P. Schmitt, Norman P. Li, and Laura Crysel. "The Antihero in Popular Culture: Life History Theory and the Dark Triad Personality Traits." Review of General Psychology 16.2 (2012): 192-199. Jones, Daniel N., and Delroy L. Paulhus. "Introducing the Short Dark Triad (SD3): A Brief Measure of Dark Personality Traits." Assessment 21.1 (2014): 28-41. Langley, Travis. Batman and Psychology: A Dark and Stormy Knight. New Jersey: John Wiley and Sons, 2012. Loock, Kathleen. Hollywood Remaking: How Film Remakes, Sequels, and Franchises Shape Industry and Culture. Oakland: U of California P, 2024. Morrison, Grant. Supergods: Our World in the Age of the Superhero. London: Jonathan Cape, 2011. Patrick, Christopher J., Don C. Fowles, and Robert F. Krueger. "Triarchic Conceptualization of Psychopathy: Developmental Origins of Disinhibition, Boldness, and Meanness." Development and Psychopathology 21.3 (2009): 913-938. Punter, David. The Literature of Terror, Volume 1: The Gothic Tradition, Second Edition. Harlow: Pearson Education, 1996. Punter, David, and Glennis Byron. The Gothic. Oxford: Blackwell, 2004. Sánchez, Alfonso Freire, and Montserrat Vidal-Mestre. "The Concept of Anti-Hero or Anti-Heroine in Contemporary Audiovisual Transmedia." Notebooks.info 52 (2022): 246-265. Spooner, Catherine. Contemporary Gothic. London: Reaktion Books, 2006. Wang, Zhiqi. "Popular Anti-Heroes: Origin, Changes, and Influences." The International Conference on Interdisciplinary Humanities and Communication Studies, 2023. DOI: 10.54254/2753-7064/3/2022796.